2018
DOI: 10.1371/journal.pone.0192214
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular muscle regeneration in zebrafish requires late signals from Insulin-like growth factors

Abstract: Insulin-like growth factors (Igfs) are key regulators of key biological processes such as embryonic development, growth, and tissue repair and regeneration. The role of Igf in myogenesis is well documented and, in zebrafish, promotes fin and heart regeneration. However, the mechanism of action of Igf in muscle repair and regeneration is not well understood. Using adult zebrafish extraocular muscle (EOM) regeneration as an experimental model, we show that Igf1 receptor blockage using either chemical inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…proliferation of blastema cells. In contrast, during the regeneration of muscle Igf is involved late, during the differentiation of newly generated myoblasts [49,61]. Our results demonstrate that the cytokine growth factor, Midkine-a, is also involved in tissue regeneration, possibly as a generic wound signal to regulate initial burst of proliferation during the regeneration of both fin and muscle ( Fig 7A and 7B and [62]).…”
Section: Plos Onementioning
confidence: 69%
See 1 more Smart Citation
“…proliferation of blastema cells. In contrast, during the regeneration of muscle Igf is involved late, during the differentiation of newly generated myoblasts [49,61]. Our results demonstrate that the cytokine growth factor, Midkine-a, is also involved in tissue regeneration, possibly as a generic wound signal to regulate initial burst of proliferation during the regeneration of both fin and muscle ( Fig 7A and 7B and [62]).…”
Section: Plos Onementioning
confidence: 69%
“…In zebrafish, regeneration of extraocular muscles utilizes the dedifferentiation and proliferation of extant myocytes, which then differentiate into muscle cells [7,13,14,[48][49][50]. An RNAseq screen previously showed the upregulation of midkine-a during regeneration of extraocular muscle [14].…”
Section: In Midkine-a Mutants Proliferation and Regeneration Of Extrmentioning
confidence: 99%
“…1). And, as in the tail fin 26 , skeletal muscle [27][28][29] , and infarcted murine heart 34 , increased autophagosome formation is observed under electron microscopy in the cardiac ventricle tissue near the injury margin, and is gradually downregulated to basal levels as regeneration progresses. Moreover, making use of the generated transgenic line we were capable to observe a significant accumulation of the autophagic vesicles within the regenerating tissue.…”
Section: Scientific Reports |mentioning
confidence: 98%
“…First, we determined the timing of twist3 gene expression level by Western blot and found a 1.5-fold induction of twist3 as early as 3 hpi (Fig 3I and 3J). Next, we utilized an EdU incorporation assay to test the number of proliferating myoblasts post-injury, since proliferation of dedifferentiated myoblasts represents the final step of the reprogramming process [25,37]. We found that the percentage of proliferating myoblasts (EdU-positive nuclei) in twist3 MOinjected fish was significantly reduced at both 24 and 48 hpi compared to control MO-injected fish (Fig 3B, 3D, 3F and 3H).…”
Section: Inhibition Of Twist3 Reduces Cell Proliferation During Musclmentioning
confidence: 94%